af015012: Disarming Images: Art for Nuclear Disarmament - Torres, Francesc; Glaser, Milton; Bread and Roses Cultural Project; AFL-CIO; Physicians for Social Responsibility (PSR) (1983)
"Affiche van Francesc Torres en Milton Glaser uitgegeven in 1983 door Bread and Roses Cultural Project, American Federation of Labor and Congress of Industrial Organizations en Physicians for Social Responsibility voor de tentoonstelling Disarming Images: Art for Nuclear Disarmament. Afbeelding: tekening van een helm waarop: LITTLE BOY. Tekst: DISARMING IMAGES: Art for Nuclear Disarmament. An exhibition organized by Bread and Roses, the cultural project of the National Union of Hospital and Health Care Employees, AFL-CIO and Physicians for Social Responsibility, NYC. Circulated by The Art Museum Association of America; 1984-86. Supported by grants from the National Endowment for the Arts, a federal agency; The New York State Council on the Arts, United Church Board for Homeland Ministries and the following foundations: The CS Fund; The Ford Foundation; Incognito Fund; W. Alton Jones Foundation, Inc.; The J.M. Kaplan Fund, Inc.; Ruth Mott Fund; Funding Exchange/National Community Funds; The Public Concern Foundation, Inc.; Samuel Rubin Foundation, Inc.; and Albert and Bessie Warner Foundation. FRANCESC TORRES War Head and/or Trans-Historical Helmet. 1983 ©. Charcoal, pastel and conté on paper 82 x 60. Collection of the artist. Design by Milton Glaser. FULL TEXT AVAILABLE AT AMSAB-ISH"